Scientific Validation of the Medicinal Efficacy of Tinospora cordifolia. (23rd December 2013) - Mishra, Amita; Kumar, Shashank; Pandey, Abhay K.
Abstract : Present communication reports the scientific evaluation of Tinospora cordifolia for its medicinal efficacy which includes phytochemical screening, antimicrobial, antioxidant, and anticancer activities of the plant. Secondary metabolites including anthraquinones, terpenoids, and saponins were present in many extracts in addition to phenolics. Total phenol contents in various extracts were found in the range of 8.75–52.50 catechol equivalent per gram (CE/g). In disc diffusion assays, polar extracts exhibited considerable inhibition against Klebsiella pneumoniae . Several other extracts also showed antibacterial activity against pathogenic strains of E. coli, Pseudomonas spp., and Proteus spp. Minimum bactericidal concentration (MBC) values of potential extracts were found between 1.29 and 22.73 mg/mL. The lowest MBC (1.29 mg/mL) was recorded for acetone and ethyl acetate extracts against K. pneumoniae and Pseudomonas spp., respectively. The antioxidant activity of the extracts was comparable to that of standard antioxidants and concentration-dependent response was shown in reducing power assay. Aqueous extracts demonstrated substantial metal ion chelating activity (67–95%) at lower concentrations (10–40  μ g/mL). Other extracts also exhibited considerable metal chelating response. Most of the extracts revealed considerable inhibition of MCF-7 cancer cell line. The study established remarkable antibacterial, antioxidant, and anticancer potential in T. cordifolia stem extracts.